Carbon Leakage with International Technology Spillovers - Reyer Gerlagh; Onno Kuik (Fondazione Eni Enrico Mattei (FEEM), 2007)
In this paper we study the effect of international technology spillovers on carbon leakage. We first develop and analyse two simple competing models for carbon leakage. The first model represents the pollution haven hypothesis. It focuses on the international competition between firms that produce energy-intensive goods. The second model highlights the role of a globally integrated carbon-energy market. We calculate formulas for the leakage rates in both models and, through meta-analysis, show that the second model captures best the major mechanisms reported in the CGE literature on carbon leakage. We extend this model with endogenous energy-saving technology and international technology spillovers. This feature is shown to decrease carbon leakage. We build-in the endogenous energy-saving technology in a large CGE model and verify that the results from the formal model carry over. Carbon leakage becomes negative for moderate levels of international technology spillover.
Keywords: F18; O39; Q25; Q4; 330; arbon-Leakage; Climate Policy; Induced Technological Change; Trade and Environment; Luftverunreinigung; Kohlendioxid; Klimaschutz; Technischer Fortschritt; Spillover-Effekt; Energiesparen; Allgemeines Gleichgewicht; Theorie